Study of production optimization and effect of hydroxyl gas on a CI engine performance and emission fueled with biodiesel blends. (7th September 2016) - Masjuki, H.H.; Ruhul, A.M.; Mustafi, Nirendra N.; Kalam, M.A.; Arbab, M.I.; Rizwanul Fattah, I.M.
Abstract: Depletion and environmental impacts of the fossil fuel are the major concerns to think about the alternative energy sources to reduce the load on petroleum fuel. Researchers worldwide are working years to improve the biodiesel fuel economy and emission characteristic. At the same time, they are working on fuel development so that can be used in the IC engine without significant modification in vehicle design. Among different alternative fuels biodiesel as well as hydroxyl gas (HHO, also known as Oxyhydrogen gas) are renewable, recyclable and non-polluting fuel. In this study, HHO gas has been introduced with ordinary diesel (OD) and 20% (v/v) palm biodiesel blended with OD (PB20) for evaluating the engine performance and emission characteristics. Optimum yield of HHO was found using single anode and two cathodes from a solution containing 1% KOH and 100 ml of water producing 2150 cc of HHO gas when electrolysis was carried out for 15 min. Using the HHO generator, about 2% more power and 5% less consumption was observed for biodiesel blended fuel in a single cylinder CI engine at full load variable speed operating conditions. Besides, on an average 20% and 10% reduction of CO and HC emission were observed respectively. Highlights: HHO gas production investigated varying different parameter of the designed electrolyzer. Optimum yield was investigated at 1% KOH, 3E (50 mm) arrangement. Performance, emission on IC engine was investigated with PB20, OD + HHO and PB20 + HHO. 20% and 10% reduction of CO and HC emission were obtained in this investigation.